Analysis of Antenatal Care by Maternal to Health Services Utilization in Working Area of Cot Girek Health Centre - Fauzah Ardah; Razia Begum Suroyo; Mangatas Silaen; Lucia Lastiur (Newinera Publisher, 2021)
According to Minister of Health Regulation (Permenkes) No. 43 of 2016 every maternal must get antenatal services according to the standard which provided to pregnant women at least 4 times during pregnancy with a schedule of one first trimester, one second trimester and two-third trimesters. The purpose of this study was to determine and analyze the influence of knowledge, attitudes, education, parity, income, support of health workers, a distance of health services and maternal health to the utilization of health services in the working area of the Cot Girek health centre, a population of this study amounted 512 people and 83 respondents were taken as the sample of this study. The research was Quantitative research used Mixed Method. The results showed of knowledge p = 0.000, education p = 0.000, income p = 0.000, support of health workers p = 0.000 shows a relationship to the utilization of health services. While attitudes p = .609, parity p = .823, distance of health services p = .167, maternal health p = .386 showed no relationship to the utilization of health services. The conclusion in this study is the influence of knowledge, education, income and support of health workers on the utilization of health services found, while the attitudes, parity, distance of health services and maternal health have no found about relationship to the utilization of health services. This research can be used as information for health workers to be more active in promoting antenatal care programs.